Conocimiento y comercialización de chayote (Sechium edule (jacq.) sw.), en los mercados de Valles Centrales de Oaxaca, México (Revista Brasileira de Agroecologia, 2014)
This study aimed to document the knowledge and marketing of chayote (Sechium edule (Jacq.) Sw) in the major markets in the Central Valleys region of Oaxaca, Mexico. The information was obtained through ethnographic methods: direct observation, participant observation with open and semi-structured interviews, and through direct interviews to purchase technical producer-sellers. Key informants were selected to describe the main aspects of traditional crop management, different uses of fruits, and marketing. Through interviews and direct observation, additional information identified aspects of local knowledge, different names, meanings, crop ecology, presence, and abundance in the markets. We found that in the Central Valleys region of Oaxaca has a broad knowledge of traditional chayote, production is in home gardens and is grown and marketed by women. The selection and classification of chayote fruit is by size, color, texture, consistency and quantity of wool. The diversity found can be attributed to the growing conditions of the region from Central Valleys of Oaxaca, in addition to the selection criteria, exchange of germplasm enter allogamous producers and status of the species. The central market and Zaachila are the most important in marketing because they sell a greater diversity of Creole chayote and more producers are involved in selling, but its destination is local. It has a large traditional knowledge that has been acquired by generations which has favored the conservation of the species and its wide range, this has allowed its own system of classification that is related to the specific use for each type of chayote combined with consumer preferences.